2019
DOI: 10.1016/j.stem.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Outcompeting p53-Mutant Cells in the Normal Esophagus by Redox Manipulation

Abstract: Highlights d Cell tracking shows low-dose ionizing radiation drives differentiation in esophagus d Low-dose radiation acts via redox stress without activating the DNA repair pathway d p53 mutant cells do not differentiate after irradiation and outcompete normal cells d Antioxidant plus radiation depletes p53 mutant cells by improving normal cell fitness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 41 publications
2
79
0
1
Order By: Relevance
“…The ability to transiently increase the likelihood of progenitors generating proliferating progeny provides a rapid and robust response to injury. The down side of this adjustable progenitor fate is that it may be subverted by mutations acquired during tissue aging, leading to mutant clonal expansions that may undergo malignant transformation 22,[41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…The ability to transiently increase the likelihood of progenitors generating proliferating progeny provides a rapid and robust response to injury. The down side of this adjustable progenitor fate is that it may be subverted by mutations acquired during tissue aging, leading to mutant clonal expansions that may undergo malignant transformation 22,[41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of p53, this function may act to help to eliminate damaged cells from the epidermal stem cell pool without inducing apoptosis, which could comprise the barrier function of squamous epithelial surfaces. Consistent with this idea, recent work has shown that low-dose radiation induces the differentiation of esophageal squamous cells at the expense of self-renewal in vivo (Fernandez-Antoran et al, 2019). TP53 and Notch genes are frequently comutated in squamous carcinomas of the skin (as in our model system) and other sites; although co-mutation of tumor suppressor genes in a particular cancer is typically taken as evidence of complementary anti-oncogenic activities, our work suggests that in the cases of squamous carcinoma it may reflect, at least in part, redundant Notch and p53 functions.…”
Section: Discussionmentioning
confidence: 66%
“…Another possible mechanism by which oncogenic mutants can exist in normal tissue but not cause cancer is illustrated by a study that showed that normal human esophagus contains TP53-mutant progenitors. Yet, TP53-mutant cells can be displaced from normal tissues through the improvement of the competitive fitness of wild-type progenitors by antioxidants [150].…”
Section: Sporadic Benign Conditions Associated With Alterations In "Dmentioning
confidence: 99%